Analysis of Diagnostic Learning Obstacles of Junior High School Students on Straight-Line Equations: A Systematic Literature Review - Ratu Bulkis; Sufyani Prabawanto; Tia Purniati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The straight-line equations are an important part of learning mathematics, but many junior high school students still have difficulty understanding it. This study aims to identify the forms of learning obstacles, causal factors, error patterns, and learning implications on straight-line equations material through the Systematic Literature Review (SLR) approach. The research method uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted on Google Scholar, ERIC, DOAJ, and Garuda for articles published in the 2016–2026 period. Based on the selection process, four articles met the inclusion criteria. The synthesis results show that students experience three types of learning obstacles: ontogenical, epistemological, and didactical. Epistemological obstacles are the most dominant obstacles, indicated by difficulties in understanding gradients, determining straight-line equations, and connecting graph and algebraic representations. The main causal factors include limited mastery of prerequisite concepts, still procedural understanding, limited mathematical representation skills, and a learning orientation toward the use of formulas. These findings aid in understanding learning obstacles within the Brousseau framework and form the basis for developing learning that emphasizes concept understanding, mathematical representation, and student reasoning.